Cardiac N-methyl D-aspartate Receptors as a Pharmacological Target. Issue 5 (November 2016) - Makhro, Asya; Tian, Qinghai; Kaestner, Lars; Kosenkov, Dmitry; Faggian, Giuseppe; Gassmann, Max; Schwarzwald, Colin; Bogdanova, Anna
Abstract : Abstract: This study focuses on characterization of the cardiac N-methyl D-aspartate receptors (NMDARs) as a target for endogenous and synthetic agonists and antagonists. Using isolated perfused rat hearts, we have shown that intracoronary administration of the NMDAR agonists and antagonists has a pronounced effect on autonomous heart function. Perfusion of rat hearts with autologous blood supplemented with NMDAR agonists was associated with induction of tachycardia, sinus arrhythmia, and ischemia occurring within physiological plasma concentration range for glutamate and glycine. Intracoronary administration of the NMDAR antagonists exerted an antiarrhythmic effect and resulted in bradycardia and improvement of capillary perfusion. Action of antagonists eliprodil, Ro25-6981, memantine, ketamine, and MK-801 on autonomous heart function diverged strikingly from that of L-type Ca 2+ channel blockers. Cardiac NMDAR subunit composition differed from that of neuronal receptors and was age specific and chamber specific. Transcripts of the GluN3A and GluN2D were found in all heart chambers, whereas expression of GluN1 and GluN2A and 2C was restricted to the atria. Expression of the GluN2B protein in ventricles increased markedly with age of the animals. The obtained data reveal that NMDARs are expressed in rat heart contributing to the autonomic heart rate regulation and the function of the cardiac conduction system. Abstract : Supplemental Digital Content is Available in the Text.